Spiral- and bar-driven peculiar velocities in Milky Way-sized galaxy simulations - Grand, Robert J. J.; Bovy, Jo; Kawata, Daisuke; Hunt, Jason A. S.; Famaey, Benoit; Siebert, Arnaud; Monari, Giacomo; Cropper, Mark (Monthly notices of the Royal Astronomical Society, 2015)
We investigate the kinematic signatures induced by spiral and bar structure in a set of simulations of Milky Way-sized spiral disc galaxies. The set includes test particle simulations that follow a quasi-stationary density wave-like scenario with rigidly rotating spiral arms, and Nbody simulations that host a bar and transient, corotating spiral arms. From a location similar to that of the Sun, we calculate the radial, tangential and line-of-sight peculiar velocity fields of a patch of the disc and quantify the fluctuations by computing the power spectrum from a two-dimensional Fourier transform. We find that the peculiar velocity power spectrum of the simulation with a bar and transient, corotating spiral arms fits very well to that of APOGEE red clump star data, while the quasi-stationary density wave spiral model without a bar does not. We determine that the power spectrum is sensitive to the number of spiral arms, spiral arm pitch angle and position with respect to the spiral arm. However, it is necessary to go beyond the line-of-sight velocity field in order to distinguish fully between the various spiral models with this method. We compute the power spectrum for different regions of the spiral discs, and discuss the application of this analysis technique to external galaxies.
Gesehen am 21.09.2020